A framework for the analysis of coupled-physics models using adaptive multi-level techniques - Turan, Erhan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
This object of this study is to develop a computational framework to analyze coupled-physics problems within the context of multi-level methods. Adaptive solution strategies in conjunction with Newton-Krylov and Domain Decomposition Methods are used to investigate different problems. Two model coupled-physics problems are selected for simulation: a fluid-structure interaction problem and a multiphase flow problem. First problem is on the deformation of a bimetallic strip exposed to natural convection. Two non-conforming and overlapping domains are created to handle the changes on the boundaries so that the deflection of the solid is applied only some portion of the fluid region. Displacements on the strip are calculated using decoupled thermoelasticity with plane strain assumption. In the second problem, collapse of a water column into the air is modeled. The interface is tracked using the Volume of Fluid method and the results are compared against experimental studies. To let the physics interact with each other and to unify different numerical solution methods, a solver called DEMONA (Decomposition Enhanced Mechanics Optimized Numerical Analysis) is developed which is verified on numerous benchmark problems. A new technique, based on an idea to reduce the solution sets is implemented into the solver, as well. With this methodology, the unknowns are filtered using various reduction criteria which are either applied in run-time or decided prior to the computations so that a specific solution approach is employed. Consequently, an adaptive strusture is attained and different solution techniques are allowed to be tested with a single model definition.
Keywords: Fluid dynamics.